Determination of Respiration Rates in Water with Sub-Micromolar Oxygen Concentrations - Garcia-Robledo, Emilio; Borisov, Sergey; Klimant, Ingo; Revsbech, Niels P. (Frontiers in Marine Science, 2016)
It is crucial for our study and understanding of element transformations in low-oxygen waters that we are able to reproduce the in situ conditions during laboratory incubations to an extent that does not result in unacceptable artefacts. In this study we have explored how experimental conditions affect measured rates of O2 consumption in low-O2 waters from the anoxic basin of Golfo Dulce (Costa Rica) and oceanic waters off Chile-Peru. High-sensitivity optode dots placed within all-glass incubation containers allowed for high resolution O2 concentration measurements in the nanomolar and low µmolar range and thus also for the determination of rates of oxygen consumption by microbial communities. Consumption rates increased dramatically (from 3 and up to 60 times) by prolonged incubations, and started to increase after 4-5 hours in surface waters and after 10-15 h in water from below the upper mixed layer. Estimated maximum growth rates during the incubations suggest the growth of opportunistic microorganism with doubling times as low as 2.8 and 4.6 h for the coastal waters of Golfo Dulce (Costa Rica) and oceanic waters off Chile and Peru, respectively. Deoxygenation by inert gas bubbling led to increases in subsequently determined rates, possibly by liberation of organics from lysis of sensitive organisms, particle or aggregate alterations or other processes mediated by the strong turbulence. Stirring of the water during the incubation led to an about 50% increase in samples previously deoxygenated by bubbling, but had no effect in untreated samples. Our data indicate that data for microbial activity obtained by short incubations of minimally manipulated water are most reliable, but deoxygenation is a prerequisite for many laboratory experiments, such as determination of denitrification rates, as O2 contamination by sampling is practically impossible to avoid.